What is the Importance of Spiritual Intelligence and Management Commitment in Business in the Era of a Pandemic? - Husni Mubarok; Djoko Soelistya; Tri Cicik Wijayanti; Rahmat Agus Santoso; Mu'minatus Sholichah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Covid-19 pandemic has become a major challenge for the national fisheries sector in Indonesia. Short and long-term impacts due to the pandemic have the potential to significantly reduce production results from production processes that are not in accordance with the targets requested by the organization, and this results in changes in governance in the organization.” In the last 3 years, during the pandemic, frozen food companies experienced a decline in the performance of their managers since there were changes in existing management governance and also experienced a decrease in motivation through the level of desire to leave the company which was still there and this is supported by recording data regarding the turnover rate for employees. the managers. This study aims to analyze the influence of spiritual intelligence on the performance of managers in frozen food companies, through the work motivation of managers, using quantitative methods with a population of 60 managers in frozen food companies with SmartPLS 3.0 analysis. The results of the study show that the influence of (1) Spiritual Intelligence has an influence on the manager's performance; (2) Management commitment has no effect on manager performance, (3) Spiritual Intelligence has an influence on work motivation; (4) Management commitment has an influence on work motivation; (5) Motivation does not affect the manager's performance; (6) Spiritual Intelligence can affect the performance of managers directly, although without going through the mediation of motivation; so from this it shows that the company should pay attention and continue to carry out moral improvement activities such as spiritual activities before work and increase the provision of moral moral guidance to its managers.